SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JENIS ANJING PELIHARAAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEB - Calvin Alexander; Bagus Mulyawan; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
The Dog Breed Decision Support System is a Web Application made using the Simple Additive Weighting method. This application can give you dog breed recommendations based on user preferences. In the making of this app, the data and information of dog breeds are collected through Dogtime.com. Then, the weighting is done by the user of this app by determining the weight of each available criteria using the provided user interface which is then calculated with the Simple Additive Weighting method. The result is a relevant, personalized recommendation of dog breed for each user.